Analisis Quality of Service Jaringan Ad-Hoc Mobile pada Sistem Telemedis Berbasis Simulasi Network Simulator 3 - Herdiana, Budi; Samosir, Fajar Petrus Apris (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2022)
Health is one of the parameters for the level of human welfare. In this day and age, human life cannot be separated from technology. Starting from complicated things to simple things, using today's technology, such as the presence of smartphones. Information technology systems that are rapidly developing today are encouraging various aspects of the field of science to keep up with the times by including technology in solving problems that exist in the field of science. As in the health sector, namely the presence of telemedicine. In several health centers, the telemedicine concept has not been widely applied, therefore the authors conducted a study to design a telemedicine communication network by focusing on the analysis of the quality of service parameters of the network that was designed. There are 2 types of topologies used in this simulation. The first is a mixed topology between Point To Point topology with star topology and mesh topology which will be used as a form of topology that will be simulated using the Network Simulator 3 simulation application.